HIV-1 Disease Progression in Breast-Feeding and Formula-Feeding Mothers: A Prospective 2-Year Comparison of T Cell Subsets, HIV-1 RNA Levels, and Mortality - Otieno, Phelgona A. (2006)
BACKGROUND: There is conflicting evidence regarding the effects of breast-feeding on maternal mortality from human immunodeficiency virus type 1 (HIV-1) infection, and little is known about the effects of breast-feeding on markers of HIV-1 disease progression. METHODS: HIV-1–seropositive women were enrolled during pregnancy and received short-course zidovudine. HIV-1 RNA levels and CD4 cell counts were determined at baseline and at months 1, 3, 6, 12, 18, and 24 postpartum and were compared between breast-feeding and formula-feeding mothers. RESULTS: Of 296 women, 98 formula fed and 198 breast-fed. At baseline, formula-feeding women had a higher education level and prevalence of HIV-1–related illness than did breast-feeding women; however, the groups did not differ with respect to CD4 cell counts and HIV-1 RNA levels. Between months 1 and 24 postpartum, CD4 cell counts decreased 3.9 cells/µL/month (P< .001), HIV-1 RNA levels increased 0.005 log(10) copies/mL/month (P = .03), and body mass index (BMI) decreased 0.03 kg/m(2)/month (P< .001). The rate of CD4 cell count decline was higher in breast-feeding mothers (7.2 cells/µL/month) than in mothers who never breast-fed (4.0 cells/µL/month) (P = .01). BMI decreased more rapidly in breast-feeding women (P = .04), whereas HIV-1 RNA levels and mortality did not differ significantly between breast-feeding and formula-feeding women. CONCLUSIONS: Breast-feeding was associated with significant decreases in CD4 cell counts and BMI. HIV-1 RNA levels and mortality were not increased, suggesting a limited adverse impact of breast-feeding in mothers receiving extended care for HIV-1 infection.